The quantum universe: philosophical foundations and oriental medicine - Menas C. Kafatos; Keun-Hang Yang (Integrative Medicine Research)
The existence of universal principles in both science and medicine implies that one can explore their common applicability. Here we explore what we have learned from quantum mechanics, phenomena such as entanglement and nonlocality, the role of participation of the observer, and how these may apply to oriental medicine. The universal principles of integrated polarity, recursion, and creative interactivity apply to all levels of existence and all human activities, including healing and medicine. This review examines the possibility that what we have learned from quantum mechanics may provide clues to better understand the operational principles of oriental medicine in an integrated way. Common to both is the assertion that Consciousness is at the foundation of the universe and the inner core of all human beings. This view goes beyond both science and medicine and has strong philosophical foundations in Western philosophy as well as monistic systems of the East.